تصریف آیاتِ قرآنیہ :مقاصد وحکم (Al-Qamar, 2022)
This paper studies the insights and objectives behind the reappearance of Qur’ānic verses in the different places. It concludes that the Holy Quran is a miraculous word in terms of its specific and unique style, preservation and codification, comprehensiveness and containing numerous purposes and rules. In this style of reappearance of the verses in different places a new point and a new wisdom is provided. This style of explanation of the Holy Quran fascinates the reader, and those who recite it and listen to it, every time feels the strength and brightness of their faith and belief.
Keywords: Qur’ānic verses; reappearance; objectives; insights